High altitude stone and wood structures of northwestern Wyoming: examples from the upper Greybull River area in the central Absaroka Mountains - Kinneer, Christopher C., author; Todd, Lawrence C., 1954-, advisor; Dean, Denis J., committee member; LaBelle, Jason M., committee member; Zier, Christian J., committee member (Colorado State University. Libraries, 2007)
This thesis presents the results of archaeological investigations of seven sites with structures identified near the headwaters of the Greybull River in the Absaroka Mountains of northwestern Wyoming. These structures have in common a construction style that consists entirely of dry-laid and/or aligned locally available stone and, in some cases, wooden elements. Investigations, analyses and interpretations of high altitude stone structure sites are often framed by categorical assumptions about site and structure functions. Assumed functions often include game drives, ceremonial localities, location markers, architectural remnants, and windbreaks. These ascribed functions condition the types of data that are gathered, and thus the results of the analyses and interpretations are often self-fulfilling. No single, best, or functionally provable argument, beyond a possible association with hunting, will be provided for the newly presented sites and structures, as too little is known about the builders' cultural and/or temporal affiliations. Rather, conclusions with respect to site and/or structure function will be oriented around pattern recognition and comparative discussion.
Department Head: Kathleen A. Galvin.